(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the effectiveness of drawing lessons and ways to increase students’ interest in the subject. Examples of methods and game technologies that can be used in the classroom are also illustrated. It has been shown that game technology can also develop students’ creative abilities.